Study on bioethanol production by using oil palm trunk (opt) sap - Chai, Seng Miao (2014)
Fossil fuels were used in large quantities as a solvent and chemical feedstock in various industries. Due to limited stock of fossil fuel and rapid increase of energy demand in Malaysia, bioethanol has become a very important and necessary alternative energy source in order to replace the limited fossil fuel stock. Hence, this paper presents the study on bioethanol production by using oil palm trunk (OPT) sap which mainly focusing on substrate concentration effect toward the yield, productivity rate, and kinetic behaviour of cell growth in different substrate concentration This research was carried out by using Saccharomyces cerevisiae Kyokai No.7 in 200mL conical flask, under 30oC anaerobic condition. The research are focusing on the inoculums culture preparation, fermentation process, sample preparation, and analyzing methods. It was found that bioethanol production is increase when substrate concentration increase, from 14g/L in 60% substrate concentration, followed by 18g/L in 80% OPT sap to 22g/L in 100% OPT sap. With the highest sugar content in the medium, S. cerevisiae can produce faster ethanol production within 30 hours of fermentation duration. However, high bioethanol concentration in the process will cause the cell growth rate falls due to the product inhibition. Besides, glucose consumption rate were found out that inversely proportional to the substrate concentration whereas ethanol production rate and cell growth rate were directly proportional to the substrate concentration. Moreover, specific bioethanol production yield was found out that exceed 0.482, 0.516, and 0.465 for 60%, 80%, and 100% of substrate concentration respectively. These results will be useful in the future scale up processes